2019
DOI: 10.1038/s41536-019-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of stem cell and gene therapy ameliorates symptoms in Huntington’s disease mice

Abstract: Huntington’s disease (HD) is a dominantly inherited monogenetic disorder characterized by motor and cognitive dysfunction due to neurodegeneration. The disease is caused by the polyglutamine (polyQ) expansion at the 5′ terminal of the exon 1 of the huntingtin (HTT) gene, IT15, which results in the accumulation of mutant HTT (mHTT) aggregates in neurons and cell death. The monogenetic cause and the loss of specific neural cell population make HD a suitable candidate for stem cell and gene therapy. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…RNA interference is a gene-silencing process that uses short interfering RNA (siRNA), short hairpin RNA (shRNA), bi-functional shRNA and microRNA (miRNA). The combination of neural progenitor stem cell therapy and RNAi therapy can ameliorate symptoms in mouse models of HD [118]. In the animal models (R6/1, R62, N171-82Q, RAT AAV-HD70 d ) of HD, siRNA, shRNA, and miRNA treatments have been used to reduce neuropathology and improve motor function [6,72,104].…”
Section: Rnai Approachesmentioning
confidence: 99%
“…RNA interference is a gene-silencing process that uses short interfering RNA (siRNA), short hairpin RNA (shRNA), bi-functional shRNA and microRNA (miRNA). The combination of neural progenitor stem cell therapy and RNAi therapy can ameliorate symptoms in mouse models of HD [118]. In the animal models (R6/1, R62, N171-82Q, RAT AAV-HD70 d ) of HD, siRNA, shRNA, and miRNA treatments have been used to reduce neuropathology and improve motor function [6,72,104].…”
Section: Rnai Approachesmentioning
confidence: 99%
“…Results Reference HD iPSCs-MSNs -elevated caspase activity upon growth factor deprivation [12] HD iPSC-MSN -neuroprotective effect of CGS21680 and APEC therapeutic potential [18] HD iPSC-NPCs -higher levels of FOXO1 and FOXO4 elevated proteasome activity [19] iPSC-GABA + neurons -under treatment with memantine reversal of HD pathologic events [20] HD monkey iPSC-astrocytes -detection of numerous HD related pathologies mHTT aggregates, inefficient glutamate clearance, suppression of mitochondrial function, abnormal electrophysiology [21] Corrected HD iPSC-NPCs -after transplantation into mice model survival and differentiation of cells into the GABAergic neurons [22] iPSC-NSCs -after bilateral transplantation into mice striatum improved locomotor function [33] mice HD iPSCs/human HD iPSCs -dysregulation of ERK signaling, β-catenin phosphorylation, SOD1 accumulation and p53 expression [34] Juvenile HD-iPSCs -high number of significantly dysregulated mRNAs [35] HD iPSC-MSN -increased calcium SOC activity; treatment by quinazoline derivative -EVP4593 led to reduced activity of SOC currents and normalization of calcium transport [23] HD monkey iPSC-NPCs -under treatment with memantine, Rilizole and Methylene blue the most potent anti-apoptotic drug was Rilizole; the most effective in reduction of mTT aggregates was Methylene blue [36] Corrected HD monkey iPSC-GABA + neurons -after transplantation into mice striatum longer lifespan of HD mice model; improved behavioral and locomotor function [37] Zhang et al [12] were among the first authors to generate an iPSC-derived HD model. The researchers developed iPSCs from an HD patient displaying 72 CAG repeats, which were used to survival and differentiation of cells into the GABAergic neurons [22] iPSC-NSCs -after bilateral transplantation into mice striatum…”
Section: Model Cell Typementioning
confidence: 99%
“…Results Reference HD iPSCs-MSNs -elevated caspase activity upon growth factor deprivation [12] HD iPSC-MSN -neuroprotective effect of CGS21680 and APEC therapeutic potential [18] HD iPSC-NPCs -higher levels of FOXO1 and FOXO4 elevated proteasome activity [19] iPSC-GABA + neurons -under treatment with memantine reversal of HD pathologic events [20] HD monkey iPSC-astrocytes -detection of numerous HD related pathologies mHTT aggregates, inefficient glutamate clearance, suppression of mitochondrial function, abnormal electrophysiology [21] Corrected HD iPSC-NPCs -after transplantation into mice model survival and differentiation of cells into the GABAergic neurons [22] longer lifespan of HD mice model; improved behavioral and locomotor function [37] Zhang et al [12] were among the first authors to generate an iPSC-derived HD model. The researchers developed iPSCs from an HD patient displaying 72 CAG repeats, which were used to generate striatal neurons susceptible to cellular damage with typical characteristics of HD, such as mHTT aggregation and decreased concentrations of glutamate transporters and BDNF.…”
Section: Model Cell Typementioning
confidence: 99%
“…To evaluate whether our model can infer species from the literature that does not mention species, we hid the species mentions and substituted them with the same symbol "*SPECIES*" to simulate the document that does not mention species. For example, masking "monkey" and "mouse" in a document (Cho et al, 2019), the sentence We have established monkey NPC cell lines from induced pluripotent stem cells (iPSCs) that can differentiate into GABAergic neurons in vitro as well as in mouse brains without tumor formation.…”
Section: Inferring Species From the Literaturementioning
confidence: 99%
“…It is instructive to analyze how the attention mechanism extracts SOIs to predict species. We choose two abstracts (Zhou et al, 2017;Cho et al, 2019) to visualize the attention distribution, as shown in Figures 8, 9. When the model predicts different species, it attends to different parts of the document.…”
Section: Case Studymentioning
confidence: 99%